Vinyl Ester Composite Synthesis Reinforced with Banana Tree Fiber with the Nanofiller Addition - Darmansyah, Darmansyah; Novaringga, Adellia; Damaru, Restu; Ginting, Simparmin Br. (Universitas Negeri Semarang, 2021)
Indonesia has the potential for natural fiber wealth which is very abundant and varied therefore it is a very interesting opportunity in the development of polymer composites using natural fiber from a banana tree. To get a composite material that has strong mechanical properties, that is by adding other materials such as nanofiller (Al2O3, SiO2, and TiO2) combined with vinyl ester resin and banana tree fiber using the hand lay-up method to produce a composite that has stronger mechanical properties than fiberglass. In this research vinyl ester composite synthesis reinforced with banana tree fiber with the addition of nanofiller which aims to determine how the effect of nanofiller type and nanofiller concentration on the mechanical properties of composite and how the bonding strength of composites through SEM analysis. The results showed that for the Al2O3 nanofiller, the highest tensile strength was with a fraction of 5% with a value of 74,81 MPa with an elongation of 1,07%, for SiO2 nanofiller the highest tensile strength was with a fraction of 0,05% with a value of 89,57 MPawith an elongation of 1,20%, and for TiO2 nanofiller the highest tensile strength was with a fraction 0f 1% with a value of 75,33 MPawith an elongation of 1,05%. The results of SEM analysis show a fairly good matrix bond.